Rare and Valuable Copies from the Library of N. V. Ustyugov in the Department of Rare Books and Manuscripts of the State Public Scientific Technological Library of the SB RAS - T. A. Dragaikina (Библиосфера, 2022)
The article deals with the problem of identifying and studying personal book collections of researchers in the funds of state libraries on the example of the documents from the collection of the Soviet historian N. V. Ustyugov, stored in the department of rare books and manuscripts (RBMD) of the State Public Scientific and Technological Library of the Siberian Branch of the Russian Academy of Sciences (GPNTB SB RAS). The purpose of the article is to introduce valuable documents from this collection into scientific circulation, to attract the attention of the research community to it. The most notable documents from this collection obtained in 2018 are considered. They are: books of the XVIII – first third of the XIX centuries, belonging to the category of book monuments, the oldest of which (“Tsarstvennyj Letopisets”) was printed in 1769. In the process of studying copies stored in RBMD from the Ustyugov book collection , more than 250 books with donation records of outstanding scientists (A. A. Zimin, V. T. Pashuto, N. I. Pavlenko, A. M. Sakharov etc.) were also revealed.; records of 150 donors have been identified in total). They reflect the professional and human relations of the owner with colleagues, students, various aspects of his activities. The value of this collection as a curios reflection of a certain period of Soviet historical science is emphasized.